Is mathematics created or discovered? Pre-service teachers' perception on a classic enigma - Vita Istihapsari; Rochmad Rochmad; Isnarto Isnarto (International Journal on Education Insight, 2021)
There are many classic questions about the nature of mathematics which have been an endless debate among philosophers. One of them is about whether mathematics is created or discovered. This research aims to find out the pre-service mathematics teachers perception about the classical enigma of mathematics after joining the course of history and philosophy of mathematics education. It was a descriptive qualitative research involving 45 pre-service mathematics teachers in their first-year training. We collected the data using questionnaire and then deepened the findings using semi-structured interview. The results suggest that 40% of the respondents believed that mathematics is created, while the rest 60% believed that mathematics is discovered. The two claims have their basic reasoning in the perspective of the respondents. Those who believed that mathematics is created argued that mathematics exists because of human activities. Therefore, it will never be founded if it is not created first. Meanwhile, those who believed that mathematics is discovered tended to argue that whether or not there is human activities to prove the mathematics phenomena, it is already there as the God created it. Thus, human just discovered it, not create it. Both arguments are interesting and have a potential impact to the mathematics education practice.